PENGARUH SELF EFFICACY DAN LOCUS OF CONTROL TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Kantor Anter Aja Kota Bengkulu) - Padli Rahman Hamsa; Mardhiyah Dwi Ilhami (UM. Bengkulu, 2023)
This study entitled The Effect of Self Efficacy and Locus of Control on Employee Performance (Case Study at Anter Aja Office, Bengkulu City). The formulation of the problem in this study is Do Self Efficacy and Locus of Control Affect Employee Performance at the Anter Aja Office in Bengkulu City? The purpose of this study was to determine the effect of self-efficacy and locus of control on employee performance at the Anter Aja office in Bengkulu City. This research was conducted on Anter Aja Office Employees in Bengkulu City. The population of this study are employees at the Anter Aja Office of Bengkulu City, totaling 68 people and using quantitative methods. There are several data analysis techniques used in this study, including using instrument tests, classical assumption tests, respondent response analysis, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. From the results of the multiple linear regression test, the regression equation is as follows: Y = 2.590 + 0.239 (X1) + 0.271 (X2). The results of the tests that have been carried out can be seen that the Self efficacy variable (X1) shows tcount> ttable (3.723> 1.99714) and (sig Î± = 0.000 <0.050), and the Locus of Control variable (X2), shows tcount> ttable (3.878> 1.99714) and (sig Î± = 0.000 <0.050). The results of the F test show that the value of Fcount>Ftable is (29,601 > 3,144) and (sig Î± = 0,000 <0.050). So it can be concluded that Self Efficacy and Locus of Control have a partial or simultaneous effect on Employee Performance at the Anter Aja Office in Bengkulu City. Keywords: Self Efficacy, Locus of Control, and Employee Performance.